Epidemiological Survey of Human Alphaherpesvirus 2 (HSV-2) Infection in Indigenous People of Dourados Municipality, Central Brazil - Flávia Freitas de Oliveira Bonfim; Livia Melo Villar; Julio Croda; Solange Rodrigues da Silva; Crhistinne Cavalheiro Maymone Gonçalves; Vivianne de Oliveira Landgraf de Castro; Grazielli Rocha de Rezende Romeira; Gabriela Alves Cesar; Sabrina Moreira dos Santos Weis-Torres; Marco Aurélio Horta; Simone Simionatto; Ana Rita Coimbra Motta-Castro; et al. (Tropical Medicine and Infectious Disease, 2023)
Sexually transmitted Human alphaherpesvirus 2 (HSV-2) causes genital ulcers, especially among sexually active adolescents and adults. We estimated the exact prevalence of anti-HSV-2 antibodies and correlated it with the demographic and behavioral aspects of the Indigenous population of the Jaguapirú and Bororó villages (Dourados, Mato Grosso do Sul (MS), Brazil). In total, 1360 individuals (>18 years old) were administered serologic tests. The prevalence of anti-HSV-2 IgM was 12.9%, that of anti-HSV-2 IgG was 57.2%, and 8.5% cases tested positive for both HSV-2 IgM and IgG. The prevalence of anti-HSV-2 antibodies was higher in females (59.5%) compared to males (49%), with an OR of 0.64 (0.49–0.83). Anti-HSV-2 antibodies were found in 14.2%, 12.3%, 15.4%, and 14.5% of participants with urinary problems, genital wounds, genital warts, and urethral discharge, respectively. In summary, the seroprevalence of HSV-2 in the Indigenous population was five times higher than that reported in the general adult Brazilian population. Educational level, income level, smoking, condom use, incarceration, illicit drug abuse, the sharing of used needles and syringes without adequate disinfection, homosexual relationships, prostitution, the sexual practices among drug users, and avoidance of contraceptive methods could contribute to the facilitation of HSV-2 transmission in the Indigenous population. Our results may help develop culturally appropriate intervention programs that eliminate health-access barriers and improve the implementation of public health policies aimed at promoting information regarding and preventing, treating, and controlling HSV-2 infection in Brazilian Indigenous populations.